Milling time influence of ultrafine treated rice husk ash to pozzolanic reactivity in portlandite - Nuruddin, Muhd Fadhil; Saad, Siti Asmahani; Shafiq, Nasir; Ali, Maisarah (CRC Press, Taylor and Francis Group, 2016)
ABSTRACT: An investigation of pozzolanic reactivity of ultrafine treated rice husk ash (UFTRHA) was eval-uated using electrical conductivity measurement. This paper is aimed to identify the effect of grinding duration via high speed milling process to the pozzolanic reactivity level. This pozzolanic reactivity assessment was completed by incorporating UFTRHA powder samples prepared at several milling duration in saturated port-landite solution at 40oC. Structure of these mesoporous substances after grinding process were captured using Field Emission Scanning Electron Microscopy (FESEM) accordingly. Based on the findings, experimental re-sults analysis reveal that UFTRHA ground at 15 min has highest pozzolanic reactivity level among all speci-mens. Hence, short period of grinding is sufficient to attain huge amount of specific surface area (SSA) by us-ing high speed milling process. Excessive grinding aid i.e. 60 min produced lower specific surface area hence lower pozzolanic reactivity level. Larger amount of specific surface area leads towards vigorous and higher pozzolanic reactivity.